Modal Frustration and Periodicity Breaking in Artificial Spin Ice. Issue 42 (28th September 2020) - Puttock, Robert; Manzin, Alessandra; Neu, Volker; Garcia‐Sanchez, Felipe; Fernandez Scarioni, Alexander; Schumacher, Hans W.; Kazakova, Olga
Abstract: Here, an artificial spin ice lattice is introduced that exhibits unique Ising and non‐Ising behavior under specific field switching protocols because of the inclusion of coupled nanomagnets into the unit cell. In the Ising regime, a magnetic switching mechanism that generates a uni‐ or bimodal distribution of states dependent on the alignment of the field is demonstrated with respect to the lattice unit cell. In addition, a method for generating a plethora of randomly distributed energy states across the lattice, consisting of Ising and Landau states, is investigated through magnetic force microscopy and micromagnetic modeling. It is demonstrated that the dispersed energy distribution across the lattice is a result of the intrinsic design and can be finely tuned through control of the incident angle of a critical field. The present manuscript explores a complex frustrated environment beyond the 16‐vertex Ising model for the development of novel logic‐based technologies. Abstract : Puttock and and co‐workers investigate how the inclusion of coupled nanomagnets in an artificial spin ice structure causes an energetically favorable disruption to the magnetic periodicity upon overcoming an energy barrier. A mix of Ising and chiral domains form under a controlled perturbation protocol, which alters the collective frustrated behavior across a correlated energy landscape.